Human Resources in the Public Health Sector: Issues and Concerns in the State of Arunachal Pradesh - Biswakarma, Gangaram (Prabandhan: Indian Journal of Management, 2012)
Man is by far the most important of all factors of production. As the public health sector is purely a service sector, the human element is a critical element for it success and achievement of organizational goals. The purposed of this study is to explore the HR issues and concerns in Public Health Sector in Arunachal Pradesh. The research findings highlighted are the Health worker shortages (particularly nurses and physicians); Misdistribution/unequal distribution; Skill mix imbalance; Poor working conditions; Low-remuneration, poor compensation and retention; Inadequate professional training and production issues; Inadequate training at various levels or inadequate capacity building, limited opportunities for professional development; Rewards not linked to performance/incentives; Lack of motivation; Job security; Lack of availability at duty, accountability of staffs and Weak supervision at all levels; Performance of the workforce; Duality of roles/overburden/work load and ill-equipped; Public health human resource policy/health sector policies and the regulation; Personnel decisions (recruitment/hiring); Health human resource planning; Absence of database on HRH/accurate information on staffing; Weak Human resource management system as the serious HR issues in the state. While discussing the findings of this study, there are three options for mitigating the shortage of health workforce and other HR issues, first to increase the production of health workforce, second to attract and deploying health workforce, and third is to retain the health workforce. Further, robust HRM activities in the organization are needed and should address the medical profession education need.